(untitled) (Global Journal of Human-Social Science, 2012)
If there were animminent threat to the integrity of African states it would be the possibility of a group or region breaking away Ironically secession is one threat which few African governments want to acknowledge exists because implies giving tacit recognition to the most reprehensible behavior any group or a region can perpetrate against the state Pursuing such policy of not acknowledging the threat of succession has come at a price since it has made governments woefully unprepared to address an actual secession effectively when it occurs African governments lackadaisical response to the menace of secession is not only bad policy but also counter-intuitive The haphazard manner in which European powers spliced the continent into colonies makes every country vulnerable to potentially splitting up for myriad of reasons including a simple disagreement between a region and the central government This paper makes the assertion that a region breaking away is such an imminent threat to African countries that governments need to pay attention and commit resources to address its causes Mali splintering into halves in 2012 shows the imminency of the threat of secession and the unpredictable causes that may precipitate such as event The paper analyzes Katanga Biafra and South Sudan breaking up to underscore the unpredictably of events which may cause a country to break up